Recovery of ammonical salts from mother liquid of 2-methyl-5-nitroimidazole - Dongare, Mohan K.; Rode, C. V.; Chandorkar, J. G. (Asian Journal of Chemistry, 2008)
An attempt have been made to recover the ammonical salt (ammonium sulphate and ammonium nitrate) from the mother liquid of 2-methyl-5-nitroimidazole successfully.
Keywords: 2-methyl-5-nitroimidazole; ammonium nitrate; ammonium sulphate; Recovery